1995
DOI: 10.1128/jcm.33.12.3186-3190.1995
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivities of PCR, MicroTrak, ChlamydiaEIA, IDEIA, and PACE 2 for purified Chlamydia trachomatis elementary bodies in urine, peripheral blood, peripheral blood leukocytes, and synovial fluid

Abstract: Routine microbiological diagnosis of Chlamydia-induced reactive arthritis is based mainly on the detection of Chlamydia trachomatis with urogenital swabs or in urine. Because chlamydial antigen, rRNA, and DNA are present in low quantities in the inflamed joint, highly sensitive assays are needed to detect C. trachomatis not only at the primary site of infection but also in peripheral blood and peripheral blood leukocytes, which are suspected carriers for dissemination, and in synovial fluid. To evaluate possib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

1997
1997
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(9 citation statements)
references
References 25 publications
0
7
0
2
Order By: Relevance
“…There are some studies that reported false positive results and less specificity for antigen-EIA, indicating the need for verification of positive results by other methods such as DNA amplification ( 16 , 17 ). The variable performance of EIA for detection of C.trachomatis might be due to patient characteristics such as gender and specimen type ( 17 , 18 ). One study reported the sensitivity of EIA was 73% in endocervical swabs from women and 60% in endourethral swabs from men ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…There are some studies that reported false positive results and less specificity for antigen-EIA, indicating the need for verification of positive results by other methods such as DNA amplification ( 16 , 17 ). The variable performance of EIA for detection of C.trachomatis might be due to patient characteristics such as gender and specimen type ( 17 , 18 ). One study reported the sensitivity of EIA was 73% in endocervical swabs from women and 60% in endourethral swabs from men ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…The sensitivities of the PCR methods were determined by serial dilutions of Ct, Bb sensu stricto , Borrelia afzelii , and Borrelia garinii in synovial fluid. The median detection limit was 2 elementary bodies per ml synovial fluid by Ct PCR and 10 Borrelia organisms per ml synovial fluid by Bb PCR (23, 24). The PCR results from the UOA patients were compared with the PCR results from patients with definite RA, Lyme arthritis, and CIA according to the above‐mentioned criteria.…”
Section: Methodsmentioning
confidence: 99%
“…1996;Li et al, 1996;Liebling et al. 1994;Li et aL, 1996; J. G. Kuipers sowie angrenzender Organe und Kompartimente in der Zukunft vermutlich zunehmend Patienten mit reaktiven Arthritiden identifizieren, die an einer persistierenden Infektion extraartikulärer Organe leiden [Kuipers et al, 1995]. Die Beobachtung persistierender asymptomatischer urogenitaler C. trachomatis Infektionen zum Zeitpunkt der Arthritis [Wollenhaupt et al, 1995;Leirisalo-Repo und Repo, 19921 Häufig wird der extraartikuläre Erregernachweis nicht gelingen.…”
Section: Epidemiologie Und Genetische Dispositionunclassified